Implementation of Rural Sanitation Development Policy in Loru Village, Sigi Regency - Fransiska, Aprilia; Kurnia, Intam; Arief, Mohamed (CV RIFAINSTITUT, 2025)
This study aims to analyze the implementation of rural sanitation development policies in Loru Village, Sigi Regency, This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with local communities, village government representatives, and health workers to gain insights into sanitation policies and practices. Direct observation on site to observe the condition of sanitation facilities and environmental cleanliness. Documentation that includes policy reports, development data, and sanitation-related records. The results of the study show that although the government has invested in the development of sanitation infrastructure, the main problem lies in the low awareness of the public. Many residents still choose to throw their wishes carelessly and use unclean air, resulting in the potential for the spread of disease. Another factor that hinders the implementation of the policy is the lack of effective communication between the Health Office, Puskesmas, and the village government. Efforts to educate and increase understanding of the importance of sanitation are needed to change people's behavior. In conclusion, the implementation of the rural sanitation development policy in Loru Village has not been optimal because the main challenge is low public awareness. Increased education and coordination between the government and the community is urgently needed to increase awareness and understanding of the importance of good sanitation. A strategy that includes a participatory approach is needed to ensure that the community understands the benefits and importance of using proper sanitation facilities.